Institutional and conceptual transformations of philosophy of history - Ivanova, Ivelina; Hristov, Todor (Historein, 2013)
The paper presents the findings of two studies on the current transformations of philosophy of history. The paper claims that those transformations outline a research field more appropriately defined as historical knowledge studies, and focused on the conditions of possibility, operation, structure, institutional praxis, critical potential and political relevance of our knowledge about history. The study provides an outline of the emergence of new problems and topics in philosophy of history based on an analysis of the contents of a prominent journal crucial to the development of the field, History and Theory, which has hosted many important debates on historical knowledge since the 1960s and whose editorial policy is recognised for its pluralism. This account of the transformation of the research field is supplemented by the findings of a study of the institutional localisation and geographic distribution of university courses in philosophy of history.